(3edLC GdbVGI YfO JYGQV GdHjfGJs - (3GdHZOGOj, CHh eMeO, ZjGK GdOjf, ZGfe Hf eMeO, J(B1030(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; SHMGf ef dG MLI Cbhi ef cdGeg hHYO ajbhd ZGfe Hf eMeO GdHZOGOj gPg QSGdI aj JYGQV GdHjfGJ LeYJgG dHYV ENhGfj ef GdbVGI hbO SejJg HedLC GdbVGI YfL JYGQV GdHjfGJs
(3BNQgG (B:s
(3GdejJ hde jNJGdhG HOjhfge Ydi CMO hde jbGVhG GdOjf Yfg hdG Yf TjA efg Ke jbHVhG GdJQcIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 116s
(3eYLe GdeDdajf (B2 / 602s
(3cTa GdXfhf (B2 / 1846s
(3gOjI GdYGQajf (B1 / 812s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs